Synthesis of catalytically active peroxidase-like Fe-doped carbon dots and application in ratiometric fluorescence detection of hydrogen peroxide and glucose. Issue 20 (7th May 2019) - Zhu, Dan; Zhuo, Shujuan; Zhu, Changqing; Zhang, Ping; Shen, Weili
Abstract : Fe-CDs with peroxidase-like activities have been fabricated and applied for H2 O2 and glucose detection. Abstract : In this study, we have presented a novel strategy to fabricate fluorescent Fe-doped carbon dots (Fe-CDs) by one-step hydrothermal carbonization, using methylthymol blue sodium salt (MTB) and FeCl3 ·6H2 O as precursors. Multiple techniques were employed to characterize the properties of the obtained Fe-CDs. Importantly, the intrinsic peroxidase-like activity of the Fe-CDs was explored. Through catalyzing the oxidization of o -phenylenediamine (OPD) by hydrogen peroxide (H2 O2 ), the Fe-CDs exhibited a superior catalytic performance over horseradish peroxidase (HRP) attributed to the doped Fe elements in the Fe-CDs. By the combination of favorable fluorescence properties and excellent catalytic activities, Fe-CD based ratiometric fluorescence sensing systems toward H2 O2 and glucose have been designed in view of the inner filter effect (IFE) between Fe-CDs and 2, 3-diaminophenazine (DAP, the oxidation product of OPD). Such responses can be used for well quantifying H2 O2 and glucose in the ranges of 0–133 μM and 0–300 μM with detection limits of 0.47 and 2.5 μM (S/N = 3), respectively. The proposed sensing system has been successfully used for the assay of glucose in human serum samples, indicating great promise as a practical platform for blood glucose sensing.